Decolonizing Antiracism - Lawrence, Bonita (Social justice, 2005)
Part of a special issue on race, racism, and empire in the Canadian context. The writers explore the exclusion of Aboriginal peoples within anti-racism. Drawing on their own experiences as a member of Canada's indigenous population and an Indian immigrant, they highlight the two ways in which Canadian anti-racism participates in colonial agendas. First, they maintain that it ignores the continued colonization of the indigenous population; and second, they suggest it fails to integrate an appreciation of Canada as a colonialist state into frameworks of anti-racism. The writers seek to decolonize anti-racism theory and begin formulating a framework that might make possible dialogue between anti-racist and Aboriginal activists.